TIME IS MONEY, OR RATHER, MONEY IS TIME - Fidalgo Gallardo, Carlos (REVISTA PROCESOS DE MERCADO, 2024)
1. The medieval Franciscan monk, Peter Johnson Olivi (1248-1298), as an unexpected starting point This humble exploration of the nature of liberty, commerce, and money was prompted by the organizers of the online seminar “Rethinking solidarity”, who kindly entrusted a number of panelists, including myself, to reflect on the meaning of solidarity in relation to economy and sustainability1. When I started to work on the task assigned, I took as starting point the person and works (and, alas, the adventures and misadventures) of a half-forgotten 13th century Franciscan monk. It might seem an unlikely startingpoint, to put it mildly. However, I think it was perfectly appropriate